Boško Buha - Bauer, Branko (Yugoslavia : Centar Film Beograd, 1978)
This children’s movie celebrates the youngest Yugoslavian communist revolutionary hero, pioneer and partisan Bosko Buha. This essentially propagandistic, but well crafted and sentimental movie is based on a allegedly true story about a group of children, barely teenagers, who joined the Yugoslav partisans after they lost their whole families in the Second World War. At the beginning of the movie, the partisans want to get rid of these children, regarding them as a burden which will only slow them down. Eventually though, they let them join combat ranks and fight shoulder to shoulder with the elders. Among these, stands out Bosko Buha, played by the first Yugoslav child movie star Slavko Štimac. Buha soon becomes a legend due to his extraordinary skill in destroying German, Ustasha and Chetnik bunkers with hand grenades. Though he behaves like a real war hero, at moments of rest his true childish nature comes to the surface. In the tragic moralistic end, after many battles and exhausting marches, Bosko gets killed, but there is no doubt that he died for a good cause.
Keywords: Fiction films